EVALUASI KUALITAS AIR IRIGASI DI DAERAH GARUT BERDASARKAN pH, DHL, SUHU DAN DEBIT ALIRAN - Anita, Anita Khairunnisa (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2024)
Irrigation water quality is significantly influenced by the surrounding environmental conditions, including human activities, land-use changes, and natural factors. Evaluating water quality is a crucial step to ensure the suitability of irrigation water for agricultural needs. This study aims to determine the suitability level of water quality against irrigation water standards in Garut. The method used in this study is a descriptive quantitative approach, focusing on the status of chemical and physical situs big77 parameters based on water analysis results. The results of the study on irrigation water quality in the Garut region revealed the following: The pH value of water from Bendung Ciroyom was 7,52, indicating alkalinity; the water sample from Sumber Mata Air Sirahna was 6,51, indicating acidity; and the water sample from Bendung Ciojar was 4,89, also indicating acidity.The electrical conductivity (EC) measurement of water from Bendung Ciroyom was 196 µS/cm, indicating a very good criterion; Sumber Mata Air Sirahna sample was 268 µS/cm, categorized as good; and the Bendung Ciojar sample was 343 µS/cm, also categorized as good.The temperature measurements showed values of 29°C for Bendung Ciroyom, 28°C for Sumber Mata Air Sirahna, and 30°C for Bendung Ciojar. According to Government Regulation No. 82 of 2001, there are no specific criteria for water temperature..The water flow rate analysis showed that Bendung Ciroyom had a flow rate of 0.40 m³/s, Sirahna Spring was 0.18 m³/s, and Bendung Ciojar was 1.50 m³/s. The pH, EC, temperature, and flow rate values mostly fall within the suitable range for irrigation purposes.